Misconceptions on the Summation Symbol Subject and Solution Proposals - Ozkan, Ayten; Ozkan, Erdogan Mehmet (ELSEVIER SCIENCE BV, 2015)
The aim of the study is to determine the misconceptions of the 11th grade students on the summation symbol subject and to determine the required measures to be taken to prevent these misconceptions and also to analyze other mistakes made other than misconceptions. 11th grade students in private science high school in 2013-2014 academic year form the target population of the study. The questions directed to the students are selected from the university preparation books and magazines of some private courses and publishers. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Summatiion symbol; Misconception; Education & Educational Research; Social Sciences - Other Topics